AN ANALYSIS OF ANTIMICROBIAL AND ANTIDIABETIC FIXED DOSE COMBINATIONS BANNED IN INDIA - jitendra Hotwani; Ankita Rao (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: National regulatory authority reviewed various fixed-dose combinations (FDCs) in view of doubtful rationality status and subsequently 349 FDCs were banned in 2018. This study was conducted to analyze the antimicrobial and antidiabetic FDCs banned by the Central Drugs Standard Control Organization in India. Methods: Data were collected from the report of drugs technical advisory board subcommittee. Banned antimicrobial and antidiabetic FDCs were assessed for the following parameters – number of active pharmacological ingredients, routes of administration and dosage forms, indications for marketing, reasons for banning, and pharmacological group of FDCs. Results: Seventy antimicrobial and 25 antidiabetic FDCs were analyzed. These FDCs contained 2–7 drugs, available mostly as tablets (51.42%, 100%) in antimicrobial and antidiabetic groups, respectively. Antimicrobial FDCs were marketed most for respiratory tract infections and infection and inflammatory conditions of the skin (17, 24.28% each) while antidiabetic FDCs were marketed for Type 2 diabetes mellitus (14, 56%). The reasons for ban were pharmacodynamic (68.57%, 16%) and pharmacokinetic (20%, 40%) mismatches, lack of evidence of efficacy (7.14%, 36%), and safety concerns (4.28%, 8%) in antimicrobial and antidiabetic groups, respectively. In antimicrobial FDCs, the most common combination was that of an antibacterial with other miscellaneous drugs (like zinc, Vitamin E, serratiopeptidase, etc.) (19, 27.14%) whereas antidiabetic FDCs most commonly had biguanide with thiazolidinedione and sulfonylurea (7, 28%). Conclusion: There is a need for scrutiny of other FDCs in larger interests of patient care and prescribers should be made aware about recently banned FDCs to promote rational pharmacotherapy.